PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN ADOBE FLASH PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU DI KELAS IV SDN 101771 TEMBUNG - Maria Anggraeni Lumban Toruan; Noperita Sarinta br. Sembiring; Meri Yanti Pasaribu; Naomi Nababan; Julya Florentina Tarigan (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
This study aims to describe the quality of adobe flash assisted learning media products as learning media based on student assessment in field trials, media expert assessments, material expert assessments and educational practitioner assessments. This type of research using the Research and Development (R&D) method, through the ADDIE development model. The subjects of this study were 29 students of grade IV SDN 101771 Tembung, 1 media expert, 1 material expert and 1 education practitioner, namely grade IV teacher. There are 2 data collection instruments used in this study, namely: 1) an assessment sheet of the quality of adobe flash assisted learning media for media experts, material experts, fourth grade teachers in SDN 101771 clay, and 2) questionnaire responses of students to adobe flash assisted learning media. As a result of the validation and feasibility of the media from the four stages, the average assessment of adobe flash-assisted learning media is declared Very Good (4.9) and Very Eligible (98%) for used as a learning.Keywords: Research and Development, ADDIE Model, Adobe Flash